Radiosynthesis, quality control, biodistribution, and infection-imaging study of a new 99mTc-labeled ertapenem radiopharmaceutical - Naqvi, Syed Ali Raza; Jabbar, Tania; Alharbi, Maha A.; Noureen, Asma; Alharbi, Nada K.; Sherazi, Tauqir A.; Shahzadi, Anum; Ahmed, Ahmed Ezzat; Afzal, M. Shahzad; Imran, M. Babar (Frontiers in Chemistry, 2022)
The accurate and cost effective diagnosis of deep-seated bacterial infections, such as urinary tract, intra-abdominal, osteomyelitis and post-surgical gynecologic infections can facilitate effective treatment. This study assessed the quality control and biological parameters of new radio-imaging agent, 99mTc-ertapenem. Ertapenem is a member of carbapenem antibiotics used for the treatment of moderate to severe intra-abdominal, urinary tract, acute pelvic, and post-surgical gynecologic infections. The antibacterial activity of ertapenem is mediated through binding to penicillin binding proteins (PBPs) which results to inhibit the cross-linking of the peptidoglycan layer of bacterial cell wall. At optimized reaction conditions, such as amount of ligand, reducing agent concentration, radioactivity and pH results 93% 99mTc-ertapenem complex yield. The 99mTc-ertapenem was found 90% intact in saline medium up to 6 h, while 88% intact in human blood serum up to 3 h. Biodistribution study showed 2.91±0.19, 2.39±0.31 and 1.23±0.22 target to non-target ratio in S. aureus, E. coli and turpentine oil infected rat models, respectively. The SPECT scintigraphy showed high uptake of 99mTc-ertapenem at bacterial infected abscesses and low counts was recorded at normal and turpentine oil inflamed tissues. 99mTc-ertapenem can be sensitive infection imaging agent, which can aid in the earlier diagnosis of deep-seated bacterial infections and treatment of wide variety of moderate to severe infections.